5(1+2x)-6x=12+9

Simple and best practice solution for 5(1+2x)-6x=12+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1+2x)-6x=12+9 equation:


Simplifying
5(1 + 2x) + -6x = 12 + 9
(1 * 5 + 2x * 5) + -6x = 12 + 9
(5 + 10x) + -6x = 12 + 9

Combine like terms: 10x + -6x = 4x
5 + 4x = 12 + 9

Combine like terms: 12 + 9 = 21
5 + 4x = 21

Solving
5 + 4x = 21

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 4x = 21 + -5

Combine like terms: 5 + -5 = 0
0 + 4x = 21 + -5
4x = 21 + -5

Combine like terms: 21 + -5 = 16
4x = 16

Divide each side by '4'.
x = 4

Simplifying
x = 4

See similar equations:

| -5x-5=-5x-4 | | -1(12x-6)=12x+6 | | -5(-5b+4)=14+8b | | 8+11=20 | | 3(3y-11)=-6(y+4) | | (4x)(7y)-(x)(3y)= | | 40=-10x | | 3x-2x+7x=-24 | | 12-17=139 | | 3y+9=5y-3y | | -2n+6n=16 | | -1.4=2x | | 25x^2+10x+-8= | | 8D=5F | | -8(3b+4)+(25b-5)=0 | | -6f+13=2f | | 5+4(3x-8)-2(x+6)=x-9 | | 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) |

Equations solver categories